The Causal Impact of Government Support on the Small Strategic Crop Industry: Malaysia’s Experience - Othman, Kamarudin; Omar, Hapiza; Fuad, Hanani Ahmad; Laidin, Jamilah; Ramli, Irlisuhayu Mohd (Asian Journal of Agriculture and Rural Development, 2020)
Rice is a staple food for countries particularly in Asia, including Malaysia, hence arise concern on its supply. Thus, this study aims to investigate the causal relationship between the incentives (fertiliser subsidy and minimum price guarantee) given and paddy production in Kedah, the rice bowl of Malaysia. A time-series data ranging from the 1996 main season to the main season in 2018 (1996H1 to 2018H1) employed. Using ARDL and Granger approaches, the result shows that any disequilibrium in paddy production is regulated to accomplish the convergence faster. In the short-run, fertiliser subsidy and paddy prices are not significant in the MADA regions. The results of the analysis show that there are various causes of the long-run in the production of rice with subsidized steel and rice prices related to rice yield. The outcome of this study demonstrates the presence of long-run causality between paddy production with fertiliser subsidy and paddy price with respect to paddy yield. Therefore, to boost the paddy yield, the government should increase the number of subsidies, and control the paddy price to prevent it from falling below the market price. Therefore, future research should investigate the causal relationship between fertiliser and paddy price subsidy to the different types of paddy seeds planted.